PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE DAN ENTERPRISE RISK MANAGEMENT TERHADAP NILAI PERUSAHAAN (Jurnal Akuntansi dan Pajak, 2023)
This study aims to examine and determine the effect of disclosure of corporate social responsibility, good corporate governance, enterprise risk management on firm value. The research method is included in quantitative research using purposive sampling method and found a sample of 35 mining companies. The data used in this research is secondary data. The data analysis method used to test the hypothesis is the multiple regression model. The results of this study indicate that Good Corporate Governance has a positive effect on firm value while Corporate Social Responsibility and Enterprise Risk Management have no effect on firm value. The conclusion in this study is that managerial share ownership in GCG provides impetus for management to act in line with the interests of stakeholders so that relationships can be established that can increase company value.